2007
DOI: 10.1111/j.1365-2745.2007.01289.x
|View full text |Cite
|
Sign up to set email alerts
|

The rhythm of savanna patch dynamics

Abstract: Summary1. Patch dynamics is a new, potentially unifying mechanism for the explanation of tree-grass coexistence in savannas. In this scale-explicit paradigm, savannas consist of patches in which a cyclical succession between woody and grassy dominance proceeds spatially asynchronously. The growing ecological and economic problem of shrub encroachment is a natural transient phase in this cycle.2. An important step towards understanding patterns at the landscape scale is achieved by investigating mechanisms at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 51 publications
1
39
0
3
Order By: Relevance
“…We have long been interested in the factors that cause recruitment of one of southern Africa's most serious encroaching species, Acacia mellifera (Ward 2005;Kraaij and Ward 2006;Wiegand et al 2006;Britz and Ward 2007;Meyer et al 2007a). We have observed that encroachment by A. mellifera is more common on rocky than on sandy substrates, although the rate of increase in encroachment is greater on sand (Britz and Ward 2007).…”
Section: Introductionmentioning
confidence: 95%
“…We have long been interested in the factors that cause recruitment of one of southern Africa's most serious encroaching species, Acacia mellifera (Ward 2005;Kraaij and Ward 2006;Wiegand et al 2006;Britz and Ward 2007;Meyer et al 2007a). We have observed that encroachment by A. mellifera is more common on rocky than on sandy substrates, although the rate of increase in encroachment is greater on sand (Britz and Ward 2007).…”
Section: Introductionmentioning
confidence: 95%
“…African Senegalia and Vachellia seeds require a critical level of soil moisture for 10-14 days before emergence, while the minimum water requirements for the first two weeks of establishment are c. 3 mm of rainfall every second day (Wilson & Witkowski, 1998) or >5 mm per week during the establishment phase (Joubert et al, 2008). Another good rainfall season or two are required for sapling survival (Meyer, Wiegand, Ward & Moustakas, 2007;Joubert et al, 2008). Multiple consecutive years of good rains may thus be necessary for successful recruitment of S. mellifera -something which may only happen a few times per century (Joubert et al, 2008).…”
Section: Ecology Of Senegalia Mellifera Relevant To the Effects Of Momentioning
confidence: 99%
“…Therefore, frequent rainfall is more important than overall mean annual precipitation in estimating tree sapling establishment (Hoffmann 1996, Wilson and Witkowski 1998, Kraaij and Ward 2006. In their patch dynamics model, Meyer et al (2007) have also explained the importance of recurring rainfall events for trees to establish.…”
Section: Introductionmentioning
confidence: 99%